Correction: Kato-Noguchi, H.; Kato, M. Invasive Characteristics of Robinia pseudoacacia and Its Impacts on Species Diversity. Diversity 2024, 16, 773 - Hisashi Kato-Noguchi; Midori Kato (Diversity)
In the originally published version of the paper [...]